Tumor budding cells, cancer stem cells and epithelial-mesenchymal transition-type cells in pancreatic cancer - Karamitopoulou, Eva (Frontiers in Oncology, 2013)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers with a 5-year survival rate of less than 5%. Moreover, PDAC escapes early detection and resists treatment. Multiple combinations of genetic alterations are known to occur in PDAC including mutational activation of KRAS, inactivation of p16/CDKN2A and SMAD4 (DPC4) and dysregulation of PTEN/PI3K/AKT signaling. Through their interaction with WNT pathway, the downstream molecules of these pathways have been implicated in the promotion of epithelial-mesenchymal transition (EMT). Emerging evidence has demonstrated that cancer stem cells (CSCs), small populations of which have been identified in PDAC, and EMT-type cells play critical roles in drug resistance, invasion and metastasis in pancreatic cancer. EMT may be histologically represented by the presence of tumor budding which is described as the occurrence of single tumor cells or small clusters (<5) of dedifferentiated cells at the invasive front of gastrointestinal (including colorectal, oesophageal, gastric and ampullary) carcinomas and is linked to poor prognosis. Tumor budding has recently been shown to occur frequently in PDAC and to be associated with adverse clinicopathological features and decreased disease-free and overall survival. The aim of this review is to present a short overview on the morphological and molecular aspects that underline the relationship between tumor budding cells, CSCs and EMT-type cells in PDAC.